Bach and Mozart essays on the enigma of genius - Marshall, Robert L. 1939- (University of Rochester Press, 2019)
Interpretive and biographical essays by a major authority on Bach and Mozart probe for clues to the driving forces and experiences that shaped the character and the extraordinary artistic achievements of these iconic composers
Title from publisher's bibliographic system (viewed on 31 Mar 2020)
Keywords: Bach, Johann Sebastian / 1685-1750 / Criticism and interpretation; Mozart, Wolfgang Amadeus / 1756-1791 / Criticism and interpretation; Luther, Martin -- 1483-1546; Bach, Johann Sebastian -- 1685-1750; Mozart, Wolfgang Amadeus -- 1756-1791; Music / 18th century / History and criticism; Komposition -- Musik; Aufsatzsammlung